Tanggung Jawab Notaris terhadap Ketidaksesuaian Akta Salinan Dengan Minuta Akta - Fidelia, Tyas; Halim, Yoefanca; Soedewo, Fricky (Kosmik Hukum, 2020)
Notary is a public official who has the authority to make authentic deeds and has other powers as referred to in this Law or based on other laws, as described in Article 1 number 1 of the Law on the Position of Notary Public. In carrying out his position, a Notary is required to act trustworthy, honest, thorough, independent, impartial, and safeguarding the interests of the parties concerned as well as making a Deed in the form of a Minute Deed. In addition, a Notary is required to issue a Grosse Akta, a Copy of the Deed, or a Quotation of the Deed based on the Minuta Deed. These matters are regulated in Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary Public. By looking at these provisions, it is fitting for a Notary to carry out his obligations. But in reality, you can still find Notaries who do not carry out the obligations as stipulated in the Law on Notary Position. Starting from negligence in maintaining the Minuta Akta to differences between the Deed of Copy and the Minuta Akta. Of course, the difference between the Deed of Copy and the Minuta of the Deed will give losses to the parties who entered into an agreement. Regarding the responsibilities of a Notary Public, in general, it can be reviewed on a civil, criminal basis, the Law on the Position of Notary Public, and the responsibility for carrying out his / her duties based on the Notary's code of ethics. By looking at this raises a problem regarding, "What is the responsibility of the Notary for the non-conformity of the Copy Deed with the Minuta Deed?". The method used in this research is a normative or juridical legal research method. Keywords: Notary, Deed, and Notary Responsibilities